Congenital Glaucoma and CHARGE Syndrome: A Case Report. Issue 2 (February 2017) - Benson, Matthew D.; Jivraj, Imran; Damji, Karim F.; Solarte, Carlos E.
Abstract : Purpose: To report a rare case of congenital glaucoma in a patient with CHARGE syndrome, present gonioscopic photographs, and explore mechanisms of disease that may account for this association. Patients and Methods: We describe a 35-week-old girl with previously diagnosed CHARGE syndrome who presented with corneal edema, buphthalmos, and elevated intraocular pressure in the left eye. She was subsequently diagnosed with congenital glaucoma and started on topical and oral therapy. Results: Examination under anesthesia confirmed the above findings as well as bilateral abnormal angles with an anterior iris insertion at the level of the posterior trabecular meshwork, prominent iris vasculature and stromal strands, and nonvisible scleral spur and ciliary body bands. Trabeculotomy and trabeculectomy were performed in the left eye with a poor outcome. CHARGE syndrome is a complex neurocristopathy, and we propose that the abnormal angle findings and associated asymmetric glaucoma in our patient share a common mechanism of neural crest cell dysfunction. Conclusions: CHARGE syndrome can be associated with congenital glaucoma and we emphasize the importance of a thorough ophthalmic examination to detect glaucoma with surgical management as deemed appropriate.